2021
DOI: 10.1111/tbed.14034
|View full text |Cite
|
Sign up to set email alerts
|

High contamination rates of shoes of veterinarians, veterinary support staff and veterinary students with Clostridioides difficile spores

Abstract: Clostridioides difficile is often found in animals and their environment. However, not much has been reported on veterinary clinics environment in terms of the spore load, prevalence and PCR ribotype diversity. The aim of this study was to assess the prevalence of C. difficile on shoe soles of veterinarians, veterinary support staff and veterinary students at the Veterinary Faculty campus. Altogether, 50 shoe sole swabs were collected, and the positivity rates ranged from 86.7% in swabs from veterinarians to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In contrast to our study where the floor isolates were dominated by RT 010 (96.6%), the most common strain identified in their study was ST 42 (likely RT 106) which represented 21.4% of their isolates (Srinivasa et al, 2019). Meanwhile, the reported prevalence of C. difficile on shoe soles collected from households ranges from 11.7% in Bangladesh to 43% in Slovenia both of which are much less than the >86.7% from the shoes of veterinary staff and students in Poland (Islam et al, 2019; Janezic et al, 2018; Wojtacka et al, 2021). While RT 010 comprised up to 73.2% of our shoe isolates, other studies reported a greater diversity of RTs with their most common RT only comprising 20%, 24%, 36% and 40%–50% of the isolates in the United States, Poland, Bangladesh and Slovenia respectively (Alam et al, 2014; Islam et al, 2019; Janezic et al, 2018; Wojtacka et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our study where the floor isolates were dominated by RT 010 (96.6%), the most common strain identified in their study was ST 42 (likely RT 106) which represented 21.4% of their isolates (Srinivasa et al, 2019). Meanwhile, the reported prevalence of C. difficile on shoe soles collected from households ranges from 11.7% in Bangladesh to 43% in Slovenia both of which are much less than the >86.7% from the shoes of veterinary staff and students in Poland (Islam et al, 2019; Janezic et al, 2018; Wojtacka et al, 2021). While RT 010 comprised up to 73.2% of our shoe isolates, other studies reported a greater diversity of RTs with their most common RT only comprising 20%, 24%, 36% and 40%–50% of the isolates in the United States, Poland, Bangladesh and Slovenia respectively (Alam et al, 2014; Islam et al, 2019; Janezic et al, 2018; Wojtacka et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, C. difficile causing infection is more likely to have originated from animals and/or the environment, suggesting this is a “One Health” problem. There are many possible routes of C. difficile transmission from the community into hospitals, including via food (Lim et al, 2018), shoe soles (Wojtacka et al, 2021), support animals (Lefebvre et al, 2006) and colonized individuals including hospital patients (Zacharioudakis et al, 2015) and staff (Friedman et al, 2013). This study investigated if C. difficile is being imported into the hospital setting from the community via contaminated shoe soles, and if clinical CDI cases could be genomically linked to hospital and/or community environmental sources.…”
Section: Introductionmentioning
confidence: 99%